Materiality and development of semiotic forms: from the hyperobject to the niche (Signifiances (Signifying), 2021)
In this contribution, we wish to highlight the role played by materiality in the constitution of semiotic forms. The notion of materiality goes beyond aspects related to the shaping of the signifying face of signs taken in isolation and directs attention towards the agency of the materials at work in any symbolic interaction. Thus, reflection on semiotic forms includes other semiotic processes and "objects" from the living to anthropic semiosis. In this framework, we will focus on the relationship between, on the one hand, the notion of "hyperobject" elaborated by the philosopher Timothy Morton within the framework of materialism and speculative realism with ecological aims, and, on the other hand, that of "niche construction" attested to in evolutionary anthropology and biosemiotics research.